2003
DOI: 10.1016/s0042-6822(03)00485-9
|View full text |Cite
|
Sign up to set email alerts
|

A block in virus-like particle maturation following assembly of murine leukaemia virus in insect cells

Abstract: Expression of the murine leukaemia virus (MLV) major Gag antigen p65(Gag) using the baculovirus expression system leads to efficient assembly and release of virus-like particles (VLP) representative of immature MLV. Expression of p180(Gag-Pol), facilitated normally in mammalian cells by readthrough of the p65(Gag) termination codon, also occurs efficiently in insect cells to provide a source of the MLV protease and a pattern of p65(Gag) processing similar to that observed in mammalian cells. VLP release from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Ϫ1 PRF also presents a target for alphaviruses: in mice, ablation of Ϫ1 PRF attenuated the symptoms of Sindbis virus (20) and VEEV (21) infections. Although less well-studied than Ϫ1 PRF, five published studies report that alteration of TCR also has negative impacts on virus replication (15,(55)(56)(57)(58). Three of these studies (55)(56)(57) examined the impact of TCR ablation in a retrovirus (murine leukemia virus).…”
Section: Chikungunya Virus Recoding Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ϫ1 PRF also presents a target for alphaviruses: in mice, ablation of Ϫ1 PRF attenuated the symptoms of Sindbis virus (20) and VEEV (21) infections. Although less well-studied than Ϫ1 PRF, five published studies report that alteration of TCR also has negative impacts on virus replication (15,(55)(56)(57)(58). Three of these studies (55)(56)(57) examined the impact of TCR ablation in a retrovirus (murine leukemia virus).…”
Section: Chikungunya Virus Recoding Signalsmentioning
confidence: 99%
“…Although less well-studied than Ϫ1 PRF, five published studies report that alteration of TCR also has negative impacts on virus replication (15,(55)(56)(57)(58). Three of these studies (55)(56)(57) examined the impact of TCR ablation in a retrovirus (murine leukemia virus). Pertinent to this study, TCR ablation was shown to reduce the pathogenicity of two alphaviruses, O'nyong-nyong and Sindbis viruses (15,58).…”
Section: Chikungunya Virus Recoding Signalsmentioning
confidence: 99%
“…VLPs have also been created from expression of the major retrovirus capsid, gag, in a number of systems including bacterial, insect and mammalian cells [111] . During the budding process, gag VLPs can be incorporated with glycoproteins present in the plasma membrane of the producer cells [112] .…”
Section: Chimeric Cov-related Vlps and Their Prospects For Vaccinesmentioning
confidence: 99%
“…Lymphocytic choriomeningitis virus-Arm53b, Pichinde virus-AN3739 and Tacaribe virus-TRVL11573 was grown on BHK-21 cells; Junin virus-Candid#1 and SARS coronavirus-Tor2 were grown on Vero-E6 cells; Porcine respiratory and reproductive syndrome virus-SD-23983 was grown on MARC145 cells; Type II Feline coronavirus was grown on AK-D cells; Mouse hepatitis virus-A59 was grown on mouse 17Cl-1 cells; Influenza A virus-Udorn/307/72 was grown on MDCK cells; Influenza B virus-Beijing/1/87 was grown in embryonated chicken eggs; and Murine leukaemia virus Gag particles were expressed in SF9 cells using a recombinant baculovirus expression system [20].…”
Section: Viruses and Cellsmentioning
confidence: 99%